OTOMATISASI RISET KATA KUNCI - Muhammad Lutfi Mahasinul Akhlak (TRANSFORMASI, 2022)
Keyword research is market research for the 21st century. Success in choosing the right and relevant keywords will make the visibility of online stores and selling products better. Keyword research is needed on all social media platforms so it requires repetition of keyword research for quite a long time because you have to open one by one the existing media platforms. Therefore a tool or tools are needed to conduct effective keyword research by combining the process of searching for keywords in one tool. The scope of this research is to create tools based on the iMacross script to increase effectiveness and efficiency in keyword searches on Google, YouTube, Facebook, Facebook Marketplace and Instagram. Research uses the Waterfall system development model, system analysis uses SWOT and Feasibility analysis uses TELOS analysis (Economic, Legal, Operational and Schedule feasibility). The results of the questionnaire (questionnaire) for system users with questions referring to the TELOS Feasibility Study show a feasibility level of 78.64%. This percentage illustrates that the system is feasible to use, easy to learn, easy to understand and effective in helping internet marketers in keyword research.Keywords: keywords, iMacros, Waterfall, SWOT, TELOS, Instagram.